Transdisciplinary approach to prevent stunting in Indonesia - Laili Rahayuwati; Desy Indra Yani; Arlette Suzy Setiawan; Myra D Oruga (Jurnal Keperawatan Padjadjaran, 2023)
Stunting remains a public health burden in Indonesia. National strategy and coordination of acceleration implementation for stunting reduction have been applied. The transdisciplinary approach is essential to improving the effectiveness and efficiency of all levels of participating in stunting programs. This transdisciplinary approach is expected to solve stunting problems from upstream to downstream and provide innovations based on local and national needs. In creating a stunting-free area, a transdisciplinary approach not only decreases stunting prevalence but also sustains children's health status.